Mobility of metals in salt marsh sediments colonised by Spartina maritima (Tagus estuary, Portugal) - Reboreda, Rosa (2009)
Chemical associations of Zn, Pb, Cu, Co and Cd were determined using a sequential extraction procedure in sediments colonised by S. maritima in three salt marshes within the Tagus estuary: Rosa´rio, Corroios and Pancas. Concentrations of these metals were also analysed in above- and belowground parts of Spartina maritima, as well as in sediments colonised by the plant. The highest metal concentrations in sediments were found in the marshes near the industrial and urban areas, whereas metal concentrations in plants were not significantly different among sites. This was thought to be a consequence of differences observed in metal bioavailability: Metals in Pancas, the least polluted location, were largely associated to easily accessible fractions for plant uptake, probably as a result of low organic matter content and high sandy fraction in sediments. S. maritima was able to induce the concentration of metals between its roots in the three salt marshes. The results obtained in this study indicate that S. maritima could be useful to induce phytostabilisation of metals in sediments, although the effectiveness to modify chemical associations is highly dependent on existing sediment parameters, and thus different results could be obtained depending on site characteristics.